Methanolic Fractions of Ornithogalum cuspidatum Induce Apoptosis in PC-3 Prostate Cancer Cell Line and WEHI-164 Fibrosarcoma Cancer Cell Line - Hamed Asadi; Mona Orangi; Dariush Shanehbandi; Zohreh Babaloo; Abbas Delazar; Leila Mohammadnejad; Fatemeh Zare Shahneh; Samira Valiyari; Behzad Baradaran (Tabriz University of Medical Sciences, 2014)
Purpose: The present study, was aimed to assess the cytotoxic effects of Ornithogalum cuspidatum methanolic fractions on PC-3, prostate cancer cells and WEHI-164, Fibrosarcoma cells. Methods: Methanolic fractions of O. cuspidatum were prepared using solid phase extraction and the cells were treated with different concentrations for 12 and 24 hours. Cytotoxicity and cell viability were measured by MTT assay. ELISA was also employed to assess the histone-associated DNA fragments and the involvement of apoptotic mechanisms. Results: 10 and 20% fractions had not significant cytotoxic effects (p>0.05) but other fractions exerted growth inhibition on both cancer cell lines (p<0.05). After 24h of incubation with 40, 60, 80 and 100% fractions, the IC50 values were: 165, 85, 65 and 45μg/ml on PC-3 cells and 200, 96, 76 and 73μg/ml against WEHI-164 cell line, respectively. ELISA results also revealed that, both cell lines had undergone apoptosis. Conclusion: It is deduced that, 80% and 100% methanolic fractions had significant anti-proliferative and apoptotic impacts on PC-3 and WEHI-164 cells in vitro and could be considered for developing chemo-preventive substances.